The Role Of Internal And External Factors On Audit Quality - Inneke Agustina; Emmy Indrayani (Jurnal Manajemen dan Keuangan, 2020)
Financial statements must be presented with information that is reasonable, reliable, and transparent, so it need to be audited by third parties. However, some cases involving external auditors often occur due to integrity inability. This research aims to analyze whether the internal (Professional Ethics, Independency, Experience) and external (Audit Tenure, Audit Fee) factors have a role or effect on Audit Quality. The analysis method used is Partial Least Square (PLS) using SmartPLS version 3.2.8. The data has been collected by questionnaires filled by 65 external auditors in South Jakarta who were selected using a purposive sampling. The results show that Professional Ethics and Audit Tenure affect significantly on Audit Quality. While Independency, Experience, and Audit Fee do not affect significantly on Audit Quality. Audit Tenure is the most dominant affected Audit Quality.